2019
DOI: 10.3390/vetsci6010018
|View full text |Cite
|
Sign up to set email alerts
|

41 Cases of Treatment of Cranial Cruciate Ligament Rupture with Porous TTA: Three Years of Follow Up

Abstract: Tibial Tuberosity Advancement (TTA) is a surgical technique based on a linear osteotomy that determines a cranial advancement of the tibial tuberosity in patients suffering from cranial cruciate ligament rupture (CCL). The aim is to neutralize the cranial tibial thrust (CTT) and to reach a 90° angle between the patellar tendon and the tibial plateau with a physiological knee extension of 135°. In our study, a Ti6AI4V ELI (Titanium Aluminium Vanadium) titanium scaffold for the Porous TTA, with excellent propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
3
21
0
1
Order By: Relevance
“…Clinical evolution was satisfactory in all cases and none of them had more displacement than the originally experienced. Trisciuzzi et al (2019) showed a very similar rate of distal longitudinal TT fractures (17.07%), but they needed to perform surgery again in one case [23]. In this study, there was one case that had a distal TT fissure in the first follow-up and lameness after rest, which could suggest unsatisfactory evolution; however it is important to note that the dog arrived after 1.5 months of lameness and already had mild OA (according to the Bioarth Scale [24]) in the preoperative radiographic study.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical evolution was satisfactory in all cases and none of them had more displacement than the originally experienced. Trisciuzzi et al (2019) showed a very similar rate of distal longitudinal TT fractures (17.07%), but they needed to perform surgery again in one case [23]. In this study, there was one case that had a distal TT fissure in the first follow-up and lameness after rest, which could suggest unsatisfactory evolution; however it is important to note that the dog arrived after 1.5 months of lameness and already had mild OA (according to the Bioarth Scale [24]) in the preoperative radiographic study.…”
Section: Discussionmentioning
confidence: 94%
“…Although, in our study, we employed a titanium scaffold consisting of a gyroid architecture with porous size of 1.5 × 2.4 mm with an elongation of 2% along the mechanical load, another study of smaller porous sizes (400–700 µm) was recently implanted in dogs’ tibiae, providing optimal osteointegration. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…Согласно литературным данным, первичная фиксация 3D-изделий выполняется разными способами. Чаще эту функцию несут на себе элементы конструкции либо дополнительные внутренние фиксаторы, выполненные в виде балок с отверстиями, винты и шурупы [40,41,42]. A.M. Crovace с соавторами в эксперименте на овцах при замещении дефекта большеберцовой кости величиной 5 см 3D-биомиметическими пористыми титановыми каркасами, в качестве фиксаторов успешно применяли накостные пластины и кортикальные винты.…”
Section: обсуждение основного результата исследованияunclassified